Effects of Metacognitive Strategies and Gender Differences on English as a Second Language (ESL) Students’ Listening Comprehension - Charanjit, Kaur Swaran Singh; Eng, Tek Ong; Dodi, Mulyadi; Tee, Tze Kiong; Wei, Lun Wong; Tarsame, Singh Masa Singh; Min Jie Chen (2022)
This study investigates the effects of metacognitive strategies and gender differences on ESL students’ listening comprehension. This study employed a mixed-method approach, specifically a quasi-experimental research design consisting of pre-test and post-test control, experimental groups and focus group interviews. Focus group interviews were conducted with the ESL students to get more information on how they applied the metacognitive strategies for listening comprehension. Sixty-two Lower Form Six students participated in this study and were selected based on a random sampling technique from two schools in the Seremban district, Malaysia. Pre-test and post-test data were analysed using the paired t-test, and data from the focus group interviews were analysed thematically. Findings revealed that the students exposed to metacognitive strategies had a significant difference in scores with t (6.175), p < .001 attained in comparison to the traditional method. However, there is no significant difference in gender influence on the effects of metacognitive strategies on students’ listening comprehension with t (60) = 0.628, p = .533 > .05. It can be inferred that gender does not influence the effect of metacognitive strategies on listening comprehension. Therefore, regardless of gender, if a student is exposed to such strategies, his or her listening comprehension will improve. Findings from the students’ interviews showed three dimensions of the metacognitive knowledge applied: person knowledge, task knowledge and strategic knowledge. Findings suggest that these metacognitive strategies should be a part of the pedagogical approach and should be mastered by teachers to assist ESL students in improving their listening comprehension.